Genetic diversity of the Russian sunflower breeding lines revealed by microsatellite loci analysis - S. Z. Guchetl; A. V. Golovatskaya; S. A. Ramazanova; A. A. Voloshko (Аграрная наука Евро-Северо-Востока, 2023)
The breeding of high-yielding sunflower varieties and hybrids requires the use of parent material with considerable genetic diversity. It can be identified using molecular genetic markers. The purpose of this study was the genotyping of sunflower lines bred by V. S. Pustovoit All-Russian Research Institute of Oil Crops (VNIIMK), developed in different ecological areas of cultivation, and to evaluate their genetic diversity using microsatellite loci. For the studies conducted in 2020-2022, there were used 23 lines from the Central experimental base (СEB), 17 lines from L.A. Zhdanov Don experimental station (DES), and 10 lines from the Armavir experimental station (AES). DNA was isolated from seedlings by the CTAB method. Samples were genotyped using 12 SSR markers. PCR products were separated in 8 % denaturing polyacrylamide gel or by capillary electrophoresis in a genetic analyzer. The main indicators of genetic diversity for all collections did not differ significantly from each other, and were moderate and increased in the collections of VNIIMK: AES – DES – CEB -the joint collection. In total there have been identified 37 alleles, an average 3.083 alleles per locus. The effective number of alleles ranged from 1.094 to 3.290 with an average value of 2.154. The values of the polymorphic information content (PIC) index ranged from 0.084 to 0.651, with an average of 0.434. The values of observed and expected heterozygosity ranged from zero to 0.071, 0.030, on average, and from 0.086 to 0.696, 0.500, on average, respectively. The number of shared alleles between different collections was 23. Molecular variation analysis revealed that most of the total variance (91 %) was due to differences between lines within each collection and 3 % to differences between collections. According to the results of the cluster analysis, the maternal lines from the collections of the CEB, DES, and AES of VNIIMK were mostly grouped into a cluster or subcluster separate from the paternal ones. The obtained results indicate a moderate genetic diversity of the studied sunflower lines of the breeding of VNIIMK and the existence of small differences between the collections.